جهود علماء الجزائر في الدعوة والإصلاح الاجتماعي من سنة 1830 إلى 1954م - بن زينب, علي (University of Eloued جامعة الوادي, 2021)
إن من الواجب علينا – نحن الخلف- أن نبرز شيئا من تراث سلفنا في العصر القريب، ألا وهو عصر الاحتلال الفرنسي، ذلك العهد العصيب الذي لم تشهد الجزائر منذ دخلها نور الإسلام عهدا مظلما مثل ما شهدته هذه الفترة؛ فترة شهدت ظلاما حالكا من طرف الاستعمار البغيض, لكنها شهدت في المقابل نورا ساطعا من طرف أبنائها المخلصين. ومن هنا جاءت هذه الدراسة لتبرز هذا المشهد في صورة مختصرة، وفي نفس الوقت كاشفة عن بعض أعمال علمائنا ومواقفهم وإنجازاتهم،من خلال جهودهم في مجالات مختلفة وميادين متعددة، علما أن هذه الدراسة ما هي إلا قطرة من بحر في وسط الميادين التي ولجوها والمعارك التي خاضوها. وإذا كان ميدان الدعوة والإصلاح وحده ميدانا فسيحا فإن البحث اقتصر على أهم جوانبه بذكر بعض النماذج . ولما كانت مرحلة التاريخ الحقيقي للاستعمار الفرنسي تبدأ من 1830 إلى 1954،ومرحلة الثورة 1954- 1962 تمثل مرحلة انتقالية أو مخضرمة لم تشمل الدراسة المرحلة الأخيرة، وعليه كان العنوان المقترح : "جـهود عـلماء الجزائر في الدعوة والإصلاح الاجتماعي :من سنة 1830 إلى 1954م " Résumé : Praise be to God, Lord of the Worlds, and prayers and peace be upon the most honorable of the Messengers, and after: It is incumbent upon us - the successor - to highlight something from the heritage of our predecessors in the recent era, which is the era of the French occupation, that difficult era in which Algeria has not witnessed, since the light of Islam entered it, a dark era as it witnessed during this period; A period that witnessed dark darkness from the side of the hateful colonialism, but it witnessed, on the other hand, a bright light on the part of its loyal sons. Hence this study came to highlight this scene in a brief form, and at the same time revealing some of our scholars’ work, stances and achievements, through their efforts in different fields and multiple fields, knowing that this study is only a drop from the sea in the middle of the fields they entered and the battles they fought. . If the field of advocacy and reform alone is a vast field, then the research was limited to its most important aspects by mentioning some examples. Since the stage of the real history of French colonialism starts from 1830 to 1954, and the stage of the revolution from 1954 to 1962 represents a transitional or veteran stage, the study did not include the last stage, and accordingly the proposed title was: “The Efforts of Algerian Scholars in Advocacy and Social Reform: From 1830 to 1954.”
أطروحة دكتوراه. تخصص الإمامة والخطابة. معهد العلوم الإسلامية. جامعة الوادي
Keywords: جهود، علماء الجزائر، الدعوة، الإصلاح الاجتماعي; Efforts, Algerian scholars, advocacy, social reform